2020
DOI: 10.7759/cureus.6898
|View full text |Cite
|
Sign up to set email alerts
|

Post-splenectomy Sepsis: A Review of the Literature

Abstract: The spleen is an intraperitoneal organ that performs vital hematological and immunological functions. It maintains both innate and adaptive immunity and protects the body from microbial infections. The removal of the spleen as a treatment method was initiated from the early 1500s for traumatic injuries, even before the physiology of spleen was properly understood. Splenectomy has therapeutic effects in many conditions such as sickle cell anemia, thalassemia, idiopathic thrombocytopenic purpura (ITP), Hodgkin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 43 publications
1
66
0
12
Order By: Relevance
“… Adjust public health clinics and physician routine immunization times, and sites, to better meet patient needs. Make efforts to grow opportunities for routine immunization, such as standing orders for immunization when patients come in contact anywhere in the health system, e.g., visits to emergency rooms or clinics as well as admissions, for instance post splenectomy (Tahir et al 2020 ). …”
Section: Detect Delivery Gaps Adapt and Adjust And Develop Multipromentioning
confidence: 99%
“… Adjust public health clinics and physician routine immunization times, and sites, to better meet patient needs. Make efforts to grow opportunities for routine immunization, such as standing orders for immunization when patients come in contact anywhere in the health system, e.g., visits to emergency rooms or clinics as well as admissions, for instance post splenectomy (Tahir et al 2020 ). …”
Section: Detect Delivery Gaps Adapt and Adjust And Develop Multipromentioning
confidence: 99%
“…30 However, splenectomized (asplenic) or hyposplenic individuals have an increased risk of infections, 28 and this can lead to severe sepsis known as overwhelming post-splenectomy infection (OPSI), which has a very high mortality rate. 31 A previous study showed that a higher Charlson comorbidity index score was significantly associated with severe sepsis/septic shock postsplenectomy. 32 Moreover, splenectomy can alter the serum cytokine profile, exacerbating the systematic inflammatory responses and injury to multiple organs.…”
Section: Discussionmentioning
confidence: 97%
“…Kawanaka et al reported that ATIII is recommended for patients at high risk for thrombotic complications, including splenectomy in patients with liver cirrhosis, and is safe and effective prophylactic methods that do not increase the risk of bleeding [26]. OPSI is a syndrome of fulminant sepsis occurring in splenectomized patients that are associated with high mortality and morbidity [28]. The pneumococcal vaccination will be mandatory.…”
Section: Discussionmentioning
confidence: 99%